IoT-Based Logistic Robot for Real-Time Monitoring and Control Patients during COVID-19 Pandemic - Hafidz, Isa; Adiputra, Dimas; Montolalu, Billy; Prastyabudi, Wahyu Andy; Widyantara, Helmy; Afandi, Mas Aly (Jurusan Teknik Elektro Universitas Andalas, 2020)
Coronavirus disease (COVID-19) is a disease that disrupts the respiratory tract and infects many people. However, until now, there is still no cure. Therefore a robot service is proposed to minimize direct contact between nurses and patients who are equipped with PPE (Personal Protective Equipment). Robot Service is a robot carrying logistics for patients in the Isolation Room. The robot is expected to be able to help medical personnel work and reduce the risk of medical personnel being exposed to the virus while in the Isolation Room. This robot has a feature to rotate and move along the hospital hallway, using either automatic or normal mode. This robot is also equipped with an Omni infrared camera that can see the environmental conditions around the robot so that it can make it easier for operators to run this robot with a Wi-Fi communication system. With this robot, medical workers can deliver the needs of patients without having to meet face to face, so that the risk of being exposed to the virus can be reduced.Keywords: Coronavirus, Hospital, Medical Personnel, RobotÂ AbstrakCoronavirus disease (COVID-19) is a disease that disrupts the respiratory tract and infects many people. However, until now, there is still no cure. Therefore a robot service is proposed to minimize direct contact between nurses and patients who are equipped with PPE (Personal Protective Equipment). Robot Service is a robot carrying logistics for patients in the Isolation Room. The robot is expected to be able to help medical personnel work and reduce the risk of medical personnel being exposed to the virus while in the Isolation Room. This robot has a feature to rotate and move along the hospital hallway, using either automatic or normal mode. This robot is also equipped with an Omni infrared camera that can see the environmental conditions around the robot so that it can make it easier for operators to run this robot with a Wi-Fi communication system. With this robot, medical workers can deliver the needs of patients without having to meet face to face, so that the risk of being exposed to the virus can be reduced.Kata Kunci: Coronavirus, Hospital, Medical Personnel, Robot